2022
DOI: 10.3390/ijerph19138156
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of the Scientific Research on Artisanal and Small-Scale Mining

Abstract: Mineral resource exploitation is one of the activities that contribute to economic growth and the development of society. Artisanal and small-scale mining (ASM) is one of these activities. Unfortunately, there is no clear consensus to define ASM. However, its importance is relevant in that it represents, in some cases, the only employment alternative for millions of people, although it also significantly impacts the environment. This work aims to investigate the scientific information related to ASM through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 302 publications
1
1
0
Order By: Relevance
“…However, the ASGM is characterized by a non-functioning management system where most workers are at their own management though some have structured system but do not care about safety and health conditions of their workers. This was confirmed by the findings of ( Veiga and Omotayo, 2020 ; Morante-Carballo et al., 2022 ) that as a reason of the booming nature of the ASGM, majority of workers do not care about their safety and health conditions. Moreover ( Armah et al., 2016 ; Pejtersen and Kristensen 2009 ), found that the ability of mining workers to self-protect and observe work-related health issues is mostly dependent on where they work.…”
Section: Discussionsupporting
confidence: 61%
“…However, the ASGM is characterized by a non-functioning management system where most workers are at their own management though some have structured system but do not care about safety and health conditions of their workers. This was confirmed by the findings of ( Veiga and Omotayo, 2020 ; Morante-Carballo et al., 2022 ) that as a reason of the booming nature of the ASGM, majority of workers do not care about their safety and health conditions. Moreover ( Armah et al., 2016 ; Pejtersen and Kristensen 2009 ), found that the ability of mining workers to self-protect and observe work-related health issues is mostly dependent on where they work.…”
Section: Discussionsupporting
confidence: 61%
“…According to Hess H., the plates move owing to the expansion of the ocean floor over the asthenosphere, a more ductile or less viscous underlying layer driven by the convective forces of the mantle [3]. The contours of tectonic plate areas are regions of high geological activity, including volcanic activity, earthquakes, and plate movements [4].…”
Section: Introductionmentioning
confidence: 99%
“…The vital role of geothermal energy necessitates a comprehensive literature review of the contributions of the scientific community and its applications in the public and industrial sectors [15,27]. Bibliometric and literature reviews provide a profound and detailed insight into this field of study, utilizing systematic tools or techniques to extract bibliographic information from databases such as Scopus and Web of Science (WoS) [28,29].…”
Section: Introductionmentioning
confidence: 99%